2014
DOI: 10.1159/000363194
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status and the Risk of Elevated C-Reactive Protein 12 Years Later

Abstract: Background/Aims: Low-grade inflammation is an independent risk factor for cardiovascular disease. Relationships between the antioxidant status and inflammatory biomarkers could give new insights into cardiovascular disease prevention. We investigated long-term associations between the antioxidant nutrient (vitamin C, α-tocopherol, β-carotene) status and C-reactive protein (CRP) in a population-based cohort. Methods: Subjects included in the French SU.VI.MAX trial study who had available data on baseline (1994-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Thus, our findings are in accordance with a review showing that a number of dietary intervention studies have provided evidence that dietary flavonoids can modulate CRP production [3]. In addition, studies have indicated that total flavonoid intake [61] or serum level of β-carotene [62] are inversely associated with serum CRP. Our results show a significant association (p for trend <0.05) between low-grade inflammation and vegetable variety but not for fruit variety, contrary to what we expected.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our findings are in accordance with a review showing that a number of dietary intervention studies have provided evidence that dietary flavonoids can modulate CRP production [3]. In addition, studies have indicated that total flavonoid intake [61] or serum level of β-carotene [62] are inversely associated with serum CRP. Our results show a significant association (p for trend <0.05) between low-grade inflammation and vegetable variety but not for fruit variety, contrary to what we expected.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of this, plasma carotenoids were associated with obesity, HDL-cholesterol, LDL-cholesterol, HbA1c, and smoking [15,48]. Another study done by Julia et al suggested that the β-carotene status was inversely associated with low-grade inflammation [49]. Another cross-sectional meta-analysis study focusing on Syndrome X respondents showed an inverse association between total plasma carotenoids and metabolic syndrome.…”
Section: Vitamin Amentioning
confidence: 99%
“…Moreover, treatment of sensitized mice with fenretinide (60mg/kg/day) prevents ovalbumin (OVA)-induced changes in arachidonic acid metabolism, oxidative stress, AHR and inflammation in the lungs(10). Consistent with potential anti-inflammatory effects of vitamin A or vitamin A sources, increased levels of carotenoids (11) or β-carotene (12) in serum have been associated with reduced levels of markers of systemic inflammation (such as C-reactive protein (CRP) and IL-6) in humans.…”
Section: Introductionmentioning
confidence: 96%